Functional network connectivity abnormalities in multiple sclerosis: Correlations with disability and cognitive impairment. (April 2018) - Rocca, Maria A; Valsasina, Paola; Leavitt, Victoria M; Rodegher, Mariaemma; Radaelli, Marta; Riccitelli, Gianna C; Martinelli, Vittorio; Martinelli-Boneschi, Filippo; Falini, Andrea; Comi, Giancarlo; Filippi, Massimo
Objective: To investigate resting state (RS) functional connectivity (FC) abnormalities within the principal brain networks in a large cohort of multiple sclerosis (MS) patients, to define the trajectory of FC changes over disease stages and their relation with clinical and structural magnetic resonance imaging (MRI) measures. Methods: RS functional magnetic resonance imaging (fMRI), clinical, and neuropsychological evaluation were obtained from 215 MS patients and 98 healthy controls. Connectivity abnormalities and correlations with clinical/neuropsychological/imaging measures were evaluated. We analyzed seed-voxel FC with seven major hubs, producing one visual/sensory, one motor, two cognitive, one cerebellar, and two subcortical networks. Results: MS patients showed reduced network average RS FC versus controls in the default-mode network. At regional level, a complex pattern of decreased and increased RS FC was found. Reduced RS FC mainly involved sensorimotor, cognitive, thalamic, and cerebellar networks, whereas increased RS FC involved visual/sensory and subcortical networks. Reduced RS FC correlated with T2 lesions. Reduced thalamic RS FC correlated with better neuropsychological performance, whereas for all remaining networks reduced FC correlated with more severe clinical/cognitive impairment. Conclusion: Increased and decreased RS FC occurs in MS and contributes to a wide spectrum of clinical manifestations. RS FC reduction is related to T2 lesions. Such a paradigm is inverted for the thalamic network.